Trends Management applied to Branding and Cultural Management - Gomes, Nelson Pinheiro (2016)
trends studies are giving their first steps in academia, after having proven themselves in the social and corporate fields. Now it is important to develop scientific models for the application of trends studies, including their major tool and discipline: coolhunting. the creation of models in this disciplinary field allows the creation of standards in the identification and continuous observation of trends, as well as their application in the generation of innovation and in decision-making insights, regarding major mindsets and consumer behavior patterns. the goal of this paper is to analyze the existing tools and perspectives on coolhunting and trends studies. therefore, the creation of a complex matrix is proposed, based on the portuguese perspective and developments in this field, with several combined models that promote the study and the application of trends on branding, without overlooking cultural management.